2023
DOI: 10.3390/horticulturae9050608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature Variation and Blue and Red LEDs on the Elongation of Arugula and Mustard Microgreens

Abstract: Recent studies using LED lighting at low to modest intensity have indicated that compared with red light, blue light can promote plant elongation in many crops as a shade avoidance response despite varying sensitivity with light environments, plant species, and growth stages. Currently, there is limited understanding of how temperature affects the blue light-mediated plant response. To clarify this point, two microgreen species (arugula and mustard) were grown indoors under two light quality × two temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 39 publications
(85 reference statements)
0
11
1
Order By: Relevance
“…We found that there are reported discrepancies in the morphological responses to blue vs. red LED light for plants under conditions other than an in vitro environment. Specifically, blue LED light was found to promote stem or leaf elongation in eggplants [ 23 , 24 ], cherry tomatoes [ 25 ], cucumber [ 26 , 27 ], watermelon [ 28 ], sesame [ 29 ], arugula [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], kale [ 30 , 32 , 33 , 34 ], cabbage [ 30 , 32 , 33 , 34 , 37 ], sunflowers [ 16 , 38 ], peas [ 39 ], calibrachoa [ 19 , 40 , 41 , 42 , 43 ], petunias [ 17 , 21 , 22 , 40 , 41 , 42 , 43 , 44 ], marigolds [ 18 , 40 , 42 , 43 ], geraniums [ 40 , 42 , 43 ], tulips [ 45 ], and wild Arabidopsis [ 46 , 47 , 48 ], compared to ...…”
Section: A Scientific Consensus Has Been Revised By Discoveries From ...mentioning
confidence: 99%
See 4 more Smart Citations
“…We found that there are reported discrepancies in the morphological responses to blue vs. red LED light for plants under conditions other than an in vitro environment. Specifically, blue LED light was found to promote stem or leaf elongation in eggplants [ 23 , 24 ], cherry tomatoes [ 25 ], cucumber [ 26 , 27 ], watermelon [ 28 ], sesame [ 29 ], arugula [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], kale [ 30 , 32 , 33 , 34 ], cabbage [ 30 , 32 , 33 , 34 , 37 ], sunflowers [ 16 , 38 ], peas [ 39 ], calibrachoa [ 19 , 40 , 41 , 42 , 43 ], petunias [ 17 , 21 , 22 , 40 , 41 , 42 , 43 , 44 ], marigolds [ 18 , 40 , 42 , 43 ], geraniums [ 40 , 42 , 43 ], tulips [ 45 ], and wild Arabidopsis [ 46 , 47 , 48 ], compared to ...…”
Section: A Scientific Consensus Has Been Revised By Discoveries From ...mentioning
confidence: 99%
“…Specifically, blue LED light was found to promote stem or leaf elongation in eggplants [ 23 , 24 ], cherry tomatoes [ 25 ], cucumber [ 26 , 27 ], watermelon [ 28 ], sesame [ 29 ], arugula [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], kale [ 30 , 32 , 33 , 34 ], cabbage [ 30 , 32 , 33 , 34 , 37 ], sunflowers [ 16 , 38 ], peas [ 39 ], calibrachoa [ 19 , 40 , 41 , 42 , 43 ], petunias [ 17 , 21 , 22 , 40 , 41 , 42 , 43 , 44 ], marigolds [ 18 , 40 , 42 , 43 ], geraniums [ 40 , 42 , 43 ], tulips [ 45 ], and wild Arabidopsis [ 46 , 47 , 48 ], compared to red LED light ( Table 1 ). On the other hand, blue LED light was observed to inhibit stem or leaf elongation in l...…”
Section: A Scientific Consensus Has Been Revised By Discoveries From ...mentioning
confidence: 99%
See 3 more Smart Citations